Sexual dysfunction predicts depressive symptoms during the first 2 years postpartum. Issue 6 (December 2018) - Chang, Shiow-Ru; Lin, Wei-An; Lin, Ho-Hsiung; Shyu, Ming-Kwang; Lin, Ming-I
Abstract: Background: The association between sexual function and depression has yet to be examined in a prospective cohort study with prolonged postpartum follow-up. Aim: We investigated whether sexual dysfunction predicted depressive symptoms during the 24-month postpartum period and examined the influence of obstetric factors. Methods: This prospective 2-year cohort study with repeated measures included 196 participants who were recruited in a medical center in Taipei, Taiwan (2010–2011). Data on participants' personal characteristics, sexual function, and depression symptoms at 4–6 weeks and at 3, 6, 12, and 24 months postpartum were collected and then assessed using the Female Sexual Function Index and the Center for Epidemiologic Studies Depression Scale. Results: After adjusting for time and covariates, women with sexual dysfunction had a 1.62-fold (95% confidence interval [CI]: 1.05–2.50-fold) higher estimated odds ratio (OR) for depressive symptoms during the entire 24 months after childbirth than did women without sexual dysfunction. Risk factors for depressive symptoms were a higher pain score (OR: 1.33, 95% CI: 1.13–1.57), a medical condition (OR: 1.65, 95% CI: 1.00–2.73), and severe perineal laceration (OR: 4.67, 95% CI: 1.37–15.92). Sexual satisfaction during the entire 24 months after childbirth (OR: 0.81, 95% CI: 0.70–0.95) and the highest personal income level (OR: 0.33, 95% CI: 0.11–0.99) were factors protecting against higher-scoring depressive symptoms. Conclusions: Our study provides robust evidence that sexual dysfunction and poor satisfaction, together with severe perineal laceration, greater pain, and a medical condition, predict depressive symptoms during the 24-month postpartum period.